Becoming-unhinged: Walking with vulnerability as a methodology of co-creating and reconnecting new forms of knowledge and possibilities. (1st March 2021) - Henderson, Linda; Burke, Geraldine; Clarke, Sharryn; Grimmett, Helen; Quinones, Gloria; Slater, Ann; Lam, Claudine
This article explores the act of walking with vulnerability as a methodology of becoming-unhinged. As walking assemblage, we walk as an assemblage, becoming-unhinged through affective points of contact with the more-than-human world. We consider the act of walking-thinking as an act that forces thought to become-unhinged and, in that moment, permitting thought to come into contact with all kinds of affective points. We move through a dreaming-soulful practice of walking-thinking along coastal treks, with cows, with the moon, with vulnerability and with frames. The meeting of land/water, a full moon, a hillside cemetery, a sculpture park and the use of blindfolds and frames challenge perception- apprehension, while a series of written texts, movement, stillness and contemplative practices activate vulnerability. Our emerging texts speak back to twenty-first-century academia, challenging its normative production of knowledge through the co-creation and re-creation of text/images, producing knowledge differently and opening up possibilities.